Penerapan Analisis Jalur Kepuasan Pengguna Terhadap Intensitas Pengguna SIMRS - Puspitasari, Trismayanti Dwi; HP, Dony Setiawan; Roziqin, Mochammad Choirur (JSINBIS (Jurnal Sistem Informasi Bisnis), 2017)
The hospital today used Hospital Management Information System (HMIS) in providing services. HMIS is an effort to present accurate information, timely and support the process of management functions and decision making in providing health services in the hospital. The research aims to apply the path analysis of user satisfaction to the intensity of HMIS users. The method used is path analysis test by assessing user perception of HMIS. The variables analyzed include user satisfaction, net-benefit and user intensity. The result of the research is information that is useful as the material of decision for the director of hospital in developing HMIS. HMIS software development is based on the needs of the hospital as a provider of health services for the community. The findings of this study are decisions based on the results of the implementation analysis of HMIS as material to develop HMIS for electronic medical records.